THE THE ROLE OF KAHFI MOTIVATOR SCHOOL IN DEVELOPING PUBLIC SPEAKING: PERAN KAHFI MOTIVATOR SCHOOL DALAM PENGEMBANGAN PUBLIC SPEAKING - Siti Holisah (Commed Jurnal Komunikasi dan Media, 2026)
This study examines the role of Kahfi Motivator School in improving public speaking skills. This is done through communication and learning methods that emphasize spiritual values. The focus of this study is on strategic planning, communication implementation, as well as learning models that aim to hone public speaker skills in educational institutions that are not academically or commercially oriented. The approach used was descriptive qualitative with a descriptive analysis design. Data were collected through semi-structured interviews, direct observation, and document analysis with purposive sampling technique to select informants. Data analysis was conducted using an inductive approach that included data reduction, data presentation, and conclusion drawing stages, also supported by triangulation of methods and data sources. The results of this study reveal that Kahfi Motivator School not only teaches public speaking techniques, but also focuses on character development, mindset, and value awareness through a combination of communication strategies, discipline, and spirituality. The learning methods applied proved effective in creating a sustainable and inclusive public speaker formation process, as well as encouraging participants to change the way they communicate. The conclusion of this research shows that success in developing public speaking skills is influenced by not only the technical aspects, but also the personalities of the participants.